Erythrocyte reduced/oxidized glutathione and serum thiol/disulfide homeostasis in patients with rheumatoid arthritis - Alisik, Murat; Alisik, Tugba; Nacir, Baris; Neselioglu, Salim; Genc-Isik, Irem; Koyuncu, Pinar; Erel, Ozcan (Elsevier BV, 2021)
Chronic inflammation and oxidative stress are the most known mechanisms in Rheumatoid Arthritis (RA) pathophysiology, which is still not fully elucidated. In this study, we evaluated oxidative status by determining intracellular reduced/oxidized glutathione (GSH/GSSG) homeostasis and serum thiol/disulfide (SH/SS) homeostasis in RA patients.A total of 152 RA patient and 89 healthy controls were included in the study. RA patients were subdivided according to disease activity score-28 (DAS-28) as active RA and remission RA. Intracellular GSH/GSSG and serum SH/SS homeostasis parameters were analyzed.Median (1st-3rd quartile values) SS/SH and GSSG/GSH percent ratio levels were significantly higher in RA patients (6.94 (6.02-8.54) and 69.8 (44.05-85.29); respectively) compared to controls (4.62 (4.15-5.46) and 34.9 (22.43-62.2); respectively) (p < 0.05 for all). SS/SH and GSSG/GSH percent ratio levels were significantly higher in active RA patients when compared to remission RA patients and controls (p < 0.05 for all). SS/SH and GSSG/GSH percent ratios were significantly increased in remission RA group compared to controls (p < 0.05 for all). DAS28 scores were positively correlated with SS/SH and GSSG/GSH percent ratios (rho = 0.259 and 0.296; respectively).These findings suggest that active intracellular and extracellular thiol group oxidation process might play a role in RA pathogenesis and further work in these areas may be warranted to show potential value of evaluating intracellular GSSG/GSH and serum SH/SS balances together in disease monitoring.
Keywords: Arthritis, Rheumatoid; Oxidative Stress; Erythrocytes; Disease-Activity; Glutathione Disulfide; Humans; Disulfides; Sulfhydryl Compounds; Oxidation-Reduction